Fungi : experimental methods in biology - Maheshwari, Ramesh (Mycology series, 2012)
Fungi are now at the forefront of research on mechanisms in gene silencing, biological rhythm, mating processes, biogenesis of intracellular organelles, adaptations to hostile habitats, structure of natural populations, and speciation. Because of their small genomes, fungi are being used in "systems biology" to understand the connections between genes, proteins, and metabolic and signaling pathways. The ease with which yeasts and fungi can be cultivated in simple nutritive media has also made these eukaryotic organisms the choice material for basic and applied research. Fungi: Experimental Methods in Biology, Second Edition presents the latest information on fungal biology generated through advances in genetics, molecular biology, and biochemistry. It gives an account of real experiments that have been carried out on the diverse lifestyles of these organisms. Following in the footsteps of its highly-praised predecessor, this book continues to be a comprehensive review of the state of our knowledge about how fungi function.